Dynamic behaviour and hydraulic performance of reaction turbines in embankment dams / Ameen Mohammed Salih Ameen - Ameen Mohammed, Salih Ameen (2018)
Dam and powerhouse operation sustainability is the main concern from the hydraulic engineering perspective. Powerhouse operation represents one of the main sources of vibration on the dam’s structure and thus evaluating the turbine performance with different water level pressures is highly significant. Draft tube downstream turbines run under high pressure and suffer from connection problems such as vibrations and pressure fluctuation. Reducing the pressure fluctuation and minimizing the principal stress which is related to undesired rational components of water in the draft tube turbine is still ongoing and requires to be resolved. In this research, a 3-D numerical turbine model with the construction of a submerged weir at the outlet of the draft tubes is developed. Secondly, an investigation for the dynamic behavior of an embanked dam due to earthquake effects is conducted. (Finally, an optimization operating turbine system is generated to reduce the principal stress). To achieve this, two different cases of fully opened gates of reaction turbines are inspected including Haditha Dam in Iraq and Temenggor Dam in Malaysia. The finding of the first agreed aim in which initiating a 1.333 m and a 1 m submerged weir for Kaplan (Haditha Dam) and Francis turbines (Temenggor Dam) was a very excellent proposition to solve the problem of negative pressure pulsation in the draft tube. In addition, the results showed that the natural frequencies decrease with the increase of the upstream water level and foundation depth. Finally, with the combination of the dam models with turbine models, a control program is generated to run the turbines inside the powerhouse based on minimizing the principal stress values in the selected nodes of the dam body, which depends on the principal stress classification.